Traditional usages, chemical metabolites, pharmacological activities, and pharmacokinetics of Boesenbergia rotunda (L.) Mansf.: a comprehensive review - Yan Wang; Juanjuan Wen; Feng Liu; Feng Liu; Xiujuan Peng; Gang Xu; Mingliang Zhang; Zhuangzhuang Huang; Zhuangzhuang Huang (Frontiers in Pharmacology)
Boesenbergia rotunda: (L.) Mansf. (family Zingiberaceae), also known as fingerroot, is a medicinal and food plant that is widely distributed in southern China, Southeast Asia, and South Asia. It is a traditional herb and spice that is also known for its beneficial effects on Qi, appetite, stagnation and pain relief. The objective of this study is to conduct a comprehensive and systematic review of the botanical characteristics, traditional applications, phytochemical metabolites, pharmacological properties, toxicology, quality control measures, pharmacokinetics, and clinical applications of B. rotunda. A bibliometric analysis of current studies on B. rotunda was also conducted to facilitate further exploration and utilization of B. rotunda in the functional food and pharmaceutical industries. These data were collected from PubMed, Web of Science, Google Scholar, China National Knowledge Infrastructure doctoral and master’s theses and other books and scientific databases by searching the keywords Boesenbergia rotunda. Phytochemical analysis has revealed the presence of flavonoids, monoterpenes, alkaloids, aromatic metabolites, phenols, and other metabolites in B. rotunda, exhibiting a wide range of biological activities such as anti-cancer, nephroprotective, anti-inflammatory, anti-bacterial, hepatoprotective, anti-obesity, and anti-oxidant effects, both in vivo and in vitro. In this paper, the research of B. rotunda is discussed in depth by combining traditional application and modern pharmacological research, aiming to provide valuable reference for the future research and practical application of B. rotunda.